1993
DOI: 10.1203/00006450-199302000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of Antioxidant Enzyme Gene Expression in the Developing Fetal Rat Lung by Prenatal Hormonal Treatments

Abstract: administration of thyrotropin-releasing hormone (TRH) or T R H plus dexamethasone (DEX) to pregnant rats accelerates lung surfactant system development in late gestation, but paradoxically depresses the normal late gestational elevation in fetal lung antioxidant enzyme (AOE) activities (Pediatr Res 30522, 1991). In these present studies, we tested whether both prenatal hormonal treatments act to depress normal fetal lung AOE development by negative regulation of AOE gene expression. We used solution hybridizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…cRNA preparation. The rat cRNA for Cu,ZnSOD, CAT, and GP were prepared as previously described (7,8). A pGEM-Blue construct a-actin cDNA (7) was used to synthesize a-actin [3H] cRNA for use as an mRNA recovery marker.…”
Section: Animals and Breedingmentioning
confidence: 99%
“…cRNA preparation. The rat cRNA for Cu,ZnSOD, CAT, and GP were prepared as previously described (7,8). A pGEM-Blue construct a-actin cDNA (7) was used to synthesize a-actin [3H] cRNA for use as an mRNA recovery marker.…”
Section: Animals and Breedingmentioning
confidence: 99%
“…Preparation of cRNA was performed as described previously (11,12). Total nucleic acids portionately with added mRNA.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…Our findings suggest that the regulation of lung AOE gene expression is complex under hyperoxic conditions. The prematurely delivered rats pretreated with TRH + DEX were previously found to have lowered lung AOE gene expression (depressed AOE activities and AOE mRNA levels) at preterm delivery at d 21 (4,5). Similarly, when examined at 2 d postnatal age after room air exposure, their pulmonary AOE mRNA levels remained lower in the premature TRH + DEX group compared with the shamtreated group.…”
Section: Survival In Hyperoxiamentioning
confidence: 84%
“…It has been previously demonstrated by our laboratories that although prenatal administration of TRH +DEX to pregnant rats accelerates surfactant system development in the late fetal lung, this same hormonal treatment significantly decreases the normal fetal lung AOE (SOD, CAT, and GP) activity elevations in late gestation (4). This hormonal effect appears to depend on a pretranslational/ transcriptional mechanism involving decreased AOE mRNA levels (5). When full-term newborn rats prenatally treated with TRH +DEX were exposed to prolonged hyperoxia, results showed that although these newborns manifested lower baseline AOE activities at birth than control term newborns, the 612 CHEN ETAL.…”
mentioning
confidence: 96%
See 1 more Smart Citation